El Desarrollo Psicosocial de los niños y niñas de la Escuela Alonso de Mercadillo y la intervenciòn del Trabajador Social - Ruales Chamba, Marìa Cristina (2015)
The present research work entitled "PSYCHOSOCIAL DEVELOPMENT OF CHILDREN FROM SCHOOL 'ALONSO flea market' and workers 'intervention Social' in which it was determined that school bullying this negatively influences the psychosocial development boys and girls, is why the following general objective was raised; Reduce bullying in children of the "Alonso de Mercadillo" school. The specific objectives, allowed to establish facilitated procedures to identify theories on the subject of psychosocial development and bullying, which helped to understand in a better way in order to study, in order to establish appropriate intervention strategies to the psychosocial development Educational Alonso of Market community. For the application of the same it resorted to the methodology of community self, which consists of five stages and only used their first three, in the first stage the subject's perception is known through observation and dialogue on how the subject perceives the problems that exist within the educational community; in the second stage all the empirical data will be captured with the help of a survey of children / as, interviewing authorities and teachers the same as he used it to learn more depth the problems that plagues this institution likewise served to the application of diagnostic and search for alternative solutions. Also the conclusions and recommendations are addressed clearly and accurately to the school authorities for their respective application in order to reduce bullying and improve the psychosocial development are described. 5 Therefore an intervention proposal that aims to change and transformation of the educational community through lectures, conducting group activities in order to strengthen the unity and solidarity, delivering leaflets on the importance of involving parents arises in the educational process of their children in order to reduce the existing problems